Curriculum Design for the Islamic Religious Education Study Program in the Era of the Industrial Revolution 4.0 - Syarnubi Syarnubi; Ahmad Syarifuddin; Sukirman Sukirman (STAI Hubbulwathan Duri, 2023)
The aim of this research is to investigate the curriculum of the Islamic Religious Education Study Programme, which is designed based on cultural principles. This curriculum design focuses on preparing graduates who possess a strong cultural background. Cultured refers to the ability of each graduate to exhibit conduct that aligns with the societal values that evolve within human communities. This study employs a descriptive qualitative research methodology, utilising a case study technique. The research was carried out in the Islamic Education Study Programme, Faculty of Tarbiyah and Teacher Training, Raden Fatah State Islamic University Palembang. The study's findings indicate that the development of a curriculum based on culture effectively promotes character education. The process of cultivating the character of students in the Islamic Education Study Programme through classroom-based teaching and learning activities. Character education is implemented by incorporating it into classroom instruction and learning activities, which foster the development of moral knowledge, moral emotions, and moral behaviours. Ultimately, the outcome of teaching and learning activities in the classroom is the cultivation of character in graduating students.